2012
DOI: 10.1155/2012/306879
|View full text |Cite
|
Sign up to set email alerts
|

Anoikis Resistance: An Essential Prerequisite for Tumor Metastasis

Abstract: Metastasis is a multistep process including dissociation of cancer cells from primary sites, survival in the vascular system, and proliferation in distant target organs. As a barrier to metastasis, cells normally undergo an apoptotic process known as “anoikis,” a form of cell death due to loss of contact with the extracellular matrix or neighboring cells. Cancer cells acquire anoikis resistance to survive after detachment from the primary sites and travel through the circulatory and lymphatic systems to dissem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
313
1
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 375 publications
(341 citation statements)
references
References 114 publications
3
313
1
5
Order By: Relevance
“…As expected, higher IRX1 mRNA expression was detected in the highly metastatic 143B cells relative to the mRNA levels in MNNG-HOS cells ( Figure 1B). Accordingly, IRX1 protein levels were also substantially upregulated in ZOSM and 143B cells, as indicated by Western blot and immunofluorescence analyses ( Figure 1C anoikis is a physiological barrier to metastasis and that resistance to anoikis may facilitate distant organ metastasis (24,25), we further examined the effect of IRX1 deletion on the anoikis of osteosarcoma cells by culturing cells on ultra-low attachment plates. After a 48-hour incubation, we found that ZOSM-shIRX1 and 143B-shIRX1 cells were more sensitive to detachment-induced apoptosis than were their scrambled controls ( Figure 3D).…”
Section: Resultsmentioning
confidence: 93%
“…As expected, higher IRX1 mRNA expression was detected in the highly metastatic 143B cells relative to the mRNA levels in MNNG-HOS cells ( Figure 1B). Accordingly, IRX1 protein levels were also substantially upregulated in ZOSM and 143B cells, as indicated by Western blot and immunofluorescence analyses ( Figure 1C anoikis is a physiological barrier to metastasis and that resistance to anoikis may facilitate distant organ metastasis (24,25), we further examined the effect of IRX1 deletion on the anoikis of osteosarcoma cells by culturing cells on ultra-low attachment plates. After a 48-hour incubation, we found that ZOSM-shIRX1 and 143B-shIRX1 cells were more sensitive to detachment-induced apoptosis than were their scrambled controls ( Figure 3D).…”
Section: Resultsmentioning
confidence: 93%
“…As such, tumor cells require resistance to anoikis to survive during cancer progression (4,5). The ability to evade anoikis is critically important during the metastatic cascade, as cancer cells are forced to survive in the absence of ECM-attachment while in the blood or lymphatic vessels.…”
Section: Introductionmentioning
confidence: 99%
“…Further analysis has confirmed the interaction between PP4c and PEA15 and demonstrates that PP4c -induced apoptosis in normal lymphocytes and T-leukemic cells is partly mediated through the direct or indirect dephosphorylation of PEA15 [23]. PEA15 is a member of the death effector domain (DED) protein family known to regulate cell proliferation, autophagy, and apoptosis [28,29]. It is implicated in the dysregulation of many signalling pathways involved in cancer progression and tumorigenesis and it has been described to act as both a tumour suppressor and a tumour promoter, dependent on its phosphorylation status [30][31][32].…”
Section: Accepted Manuscriptmentioning
confidence: 89%